MANAJEMEN SUMBER DAYA GURU DALAM UPAYA MENINGKATKAN PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR - Ade Tutty Rokhayati Rosa; Sarhindi; Eneng Komariah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze teacher resource management in enhancing character education in elementary schools through a case study at SD Negeri Gunungkembang, Cianjur Regency, and SD Negeri Cibadak, Bandung Regency. The research is based on the strategic role of teachers as the main agents of character education and the importance of effective teacher management in supporting character development. A qualitative approach with a case study method was employed, guided by G.R. Terry’s management framework, which includes planning, organizing, actuating, and controlling (POAC). Data were collected through in-depth interviews, observations, and documentation involving principals and teachers. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing. The results show that both schools have implemented character education programs and established clear goals; however, teacher development planning has not been systematically documented. In terms of organizing, task distribution related to character education has been carried out, although overlapping roles among teachers were still found. In the actuating stage, character education was implemented through role modeling, value-based learning, and positive habituation, but its application was not yet evenly practiced by all teachers. In the controlling stage, supervision and monitoring were conducted, yet follow-up actions based on evaluation results were still limited. This study concludes that teacher resource management based on the POAC framework plays a significant role in improving the effectiveness of character education in elementary schools and should be strengthened through more structured, consistent, and sustainable implementation.